2018
DOI: 10.1101/487330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Super-resolution Molecular Map of Basal Foot Reveals Novel Cilium in Airway Multiciliated Cells

Abstract: 33Motile cilia are beating machines that play a critical role in airway defense. During airway 34 cell differentiation, hundreds of motile cilia are templated from basal bodies that extend a basal 35 foot, an appendage that links motile cilia together to ensure beating coordination. This assembly 36 has thus far escaped structural analysis because its size is below the resolution limit. Here, we 37 determine the molecular architecture and identify basal foot proteins using a super-resolution-38 driven approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…They were eventually joined by the procentrioles to form the basal body patch. This was confirmed by fate-tracing centrosomal centrioles using Cen2GFP/Cen-RFP pulse-chase experiments 13 .…”
Section: An Atypical Centrosome Cycle Is Observed During Centriole Ammentioning
confidence: 78%
“…They were eventually joined by the procentrioles to form the basal body patch. This was confirmed by fate-tracing centrosomal centrioles using Cen2GFP/Cen-RFP pulse-chase experiments 13 .…”
Section: An Atypical Centrosome Cycle Is Observed During Centriole Ammentioning
confidence: 78%
“…Additionally, it will be important to understand how the same molecules organize such different basal feet in multiple cell types. Of note, recent studies using super-resolution microscopy showed slightly different relative positions of basal feet components in primary versus motile mammalian cilia (Figure 2) [53].…”
Section: Cilia: Variations Of a Basic Structure To Fulfill Myriad mentioning
confidence: 99%
“…The most proximal region (I) contains proteins that are common to the primary cilia basal feet (i.e. Centrosomal protein of 128 kDa (CEP128) and ODF2) that are most likely responsible for the scaffolding (based on proteomics and super-resolution microscopy data in [53]).…”
Section: Figurementioning
confidence: 99%
“…2b). A previous study divided the BF assembly of motile cilia into two regions, I and II 20,26 . For immature cells, we observed CNTRL in close proximity to ODF2 in the future BF region I.…”
Section: Resultsmentioning
confidence: 99%
“…For example, while outer dense fiber 2 (ODF2), which is an essential scaffold for initiating the assembly of basal feet/SDAs, appears near the centriolar wall along the transverse axis of both BF types, centriolin (CNTRL) appears near ODF2 in primary cilia but not in motile cilia. In motile cilia, CNTRL appears further away in the region where the BF tapers 20,25,26 . FGFR1 oncogene partner (FOP) is also localized to the basal feet/SDAs of primary cilia 27 , whereas its precise localization in the BB of motile cilia is unknown.…”
mentioning
confidence: 98%